2010
DOI: 10.1002/hep.23711
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Versus Fatness: Moving Beyond Weight Loss in Nonalcoholic Fatty Liver Disease

Abstract: The rapid emergence of nonalcoholic fatty liver disease (NAFLD) as a cause of both liverrelated morbidity and mortality and cardiometabolic risk has led to the search for effective lifestyle strategies to reduce liver fat. Lifestyle intervention comprising dietary restriction in conjunction with increased physical activity has shown clear hepatic benefits when weight loss approximating 3%-10% of body weight is achieved. Yet, the poor sustainability of weight loss challenges the current therapeutic focus on bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
95
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 59 publications
2
95
0
2
Order By: Relevance
“…Most published data suggest that this is the case, but these data have been derived from self-reports. 26,27 Self-reports are reliable, but the sensitivity of the data with respect to amount of time spent and level of intensity of the activity has been difficult to validate. 28 We chose to use the NHANES survey (2003-2004 and 2005-2006) because it reported data collected from an activity monitor.…”
Section: Discussionmentioning
confidence: 99%
“…Most published data suggest that this is the case, but these data have been derived from self-reports. 26,27 Self-reports are reliable, but the sensitivity of the data with respect to amount of time spent and level of intensity of the activity has been difficult to validate. 28 We chose to use the NHANES survey (2003-2004 and 2005-2006) because it reported data collected from an activity monitor.…”
Section: Discussionmentioning
confidence: 99%
“…Regular PA is known to be associated with lower total and central adiposity (17,18,26) as well as with lower insulin resistance (23,27) in children and adolescents. Therefore, it is biologically plausible that regular PA preserves the hazard effects of adiposity and insulin resistance on liver function enzymes (24,25). The increased hepatic lipogenesis and triglyceride-rich lipoprotein secretion induced by excess of central adiposity (2) might also be attenuated by regular PA, as several studies have unequivocally shown that PA is associated with a healthier blood lipid profile (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies investigating the effectiveness of regular PA on NAFLD in obese children and adolescents (29)(30)(31)(32) support weight loss in reversing the progression of NAFLD. Recent evidence also suggests that exercise may play a key role on hepatic fat content by directly altering hepatic β-oxidation and/or lipogenesis (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that dietary intervention needs to be intense, with frequent clinic visits to show a signifi cant improvement in liver histology in patients with biopsy-proven NASH. Physical activity can help maintain the weight loss and also improve IR, and recent data suggest that patients who show histological improvement tend to be more active ( 4 ). However, it has been diffi cult to differentiate the individual eff ects of physical activity and weight loss on the overall histological response in published studies.…”
mentioning
confidence: 99%